The Effectiveness of Interactive Multimedia to Improve the Career Planning Ability of Junior High School Students (Jurnal Bimbingan Konseling, 2018)
This research aims to improve the ability of junior high school students' career planning by using interactive multimedia. The experimental research method used the design of one group pre-testÂ and post-test with purposive sampling technique to determine 27 subjects of the Junior High School class IX students. The results of the research were obtained further planning career of class IX students of Public Junior High School 3 Cepu, before using guidance media (pre-test) the mean value was 109.74 with SD 3.84 and an increase in the mean posttest 153.33 with SD 3.12. The results of the t-test show that interactive multimedia is effective to improve the career planning skills of Junior High School students (t(27) = 12.58, p <0.01). This finding confirms that interactive multimedia can be applied to improve Junior High School studentsâ€™ career planning.